UPAYA ORGANISASI SOSIAL MENGANGKAT MASYARAKAT MISKIN MELALUI PROGRAM PEMBERDAYAAN - Indah Huruswati (Sosio Informa, 2003)
One among social participation forms within social welfare development can be seen in social organization or non-governmental organization. Social organization/non-governmental organization is government partner on solvingsocial problems. As a dynamic partner, hopefully, those social organization enable to be self help both in fund and management. It is also hoped that they have ability on motivate and encourage scial participation. NGOs role on conducting social welfare program, in one hand, is seen as significant on jelping grass root level society. On the other handm, they almost dependent both in program and fund. In the future, hopefully, NGOs noÂ more depended on Government, especially on conducting social welfare development. The NGOs should free from their dependency of government organzation both horizontally and vertically. Hence they enable to help grass root level society in responding social actual needs. Hopefully, NGOs program is not only in terms of charity and rehabilitation but also copes motivation processes, assistance, developmentm, advocacy and all activities in empowering society.